Performance of single axis tracker technology and automatic battery monitoring in solar hybrid systems - Satria, Habib; Nisworo, Sapto; Windarta, Jaka; B. Y. Syah, Rahmad (Institute of Advanced Engineering and Science, 2023)
Utilization of elevation angles and azimuth angles is a very important part in maximizing solar energy into electrical energy in photovoltaic (PV). One way to maximize PV power output is to design a single axis tracker system and take into account the azimuth and elevation angles of the sun using the sun position calculator application. The single axis tracker system is set based on the position of the angle of inclination of the surface of the PV 45°, then the angle of 90° and the angle of inclination of 135°. The test results show that the single axis tracker PV system design can work based on the angle settings that have been programmed. Then the use of a battery control system to support the PV reliability system automatically cuts off electricity when the battery voltage drops below 12 V during cloudy weather conditions and excessive battery usage. The integration of the PZEM-017 module with the battery will support monitoring of battery power usage in real time. PV energy data conversion performance uses single axis tracker technology for maximum power reaching 631.72 Watt DC at 12.00 pm and the lowest power reaching 56.02 Watt DC at 6.00 pm.